2018
DOI: 10.2478/jas-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Native Honey Bee Subspecies in Republic of Benin Using Morphometric and Genetic Tools

Abstract: Morphometric characteristics combined with genetic markers are powerful tools used for determining honey bee subspecies. Bees samples collected from 94 established apiaries distributed throughout all of the Republic of Benin were morphometricaly characterized using seven parameters and the COI-COII regions of mitochondrial DNA were sequenced. Based on the morphometric data the native honey bees could be divided into three distinct ecotypes - the Benino-dry-tropical-ecotype in the north, the Benino-Sudanian-eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
3
7
0
Order By: Relevance
“…1993). The absence of a P sequence was also reported from honey bees in neighboring Sudan (El-Niweiri and Moritz 2008), West African Benin (Amakpe et al 2018), and haplotype Y2 of Ethiopia (Franck et al 2001). A small fraction of the samples from this study was found to have a P 0 sequence , without a clear regional or ecological distribution pattern.…”
Section: Discussionsupporting
confidence: 63%
“…1993). The absence of a P sequence was also reported from honey bees in neighboring Sudan (El-Niweiri and Moritz 2008), West African Benin (Amakpe et al 2018), and haplotype Y2 of Ethiopia (Franck et al 2001). A small fraction of the samples from this study was found to have a P 0 sequence , without a clear regional or ecological distribution pattern.…”
Section: Discussionsupporting
confidence: 63%
“…Amakpe et al in Benin, Africa, found no correlation between morphometric characters (mainly leg and wing length) and altitude of the inspected apiaries, although they described a positive south-north gradient in bee size. Moreover, they indicated that there was no difference between the morphometric characters between the different haplotype, same results as in the present study in Nicaragua [ 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…mellifera scutellata mitotype A4. The phylogenetic analysis indicated a similarity > 99.7% to sequences from Africa [ 39 ], Brazil [ 42 ] and Argentina [ 44 ], reinforcing the findings that this mitotype is found more frequently in subtropical and tropical areas [ 42 ].…”
Section: Discussionsupporting
confidence: 65%
“…Body characteristics of worker honeybee [ 12 , 21 29 ] and their comb cell size [ 30 , 31 ] vary among subspecies. Factors that affect worker body characteristics include pollen and nectar resources [ 32 ], content of dietary protein [ 33 , 34 ], rearing season [ 35 – 37 ], geographical location [ 38 , 39 ] and level of infestation by the Varroa mite, Varroa destructor [ 37 ].…”
Section: Introductionmentioning
confidence: 99%